Плотность устьиц у сосны обыкновенной разного происхождения в географических культурах Приангарья - Кузьмин, С.Р.; Кузьмина, Н.А. (Фактори експериментальної еволюції організмів, 2008)
Stomatal density, needle length and width of different Scots pine provenances were
studied in the provenance trial. It was determined that the closest relation is between stomatal
density and needle length. Stomatal density and needle length are under great genetic control
and closely related by positive correlation. Needle width is to a greater extent under control of
temperature factor in the place of trial.